The Problem of Non-Execution of the Precautionary Attachment Decision Taken during the Enforcement of Foreign Court Decisions - Zeynep Derya Tarman (Public and Private International Law Bulletin)
Obtaining and executing a provisional attachment order during the recognition and enforcement proceeding of a foreign court judgement constitutes a significant issue in both private international law and enforcement law. Under Turkish law, rules regarding the procedure and conditions for the enforcement of foreign court judgements are regulated under the Private International Law and Procedural Law Code numbered 5718 (PIL Code) Article 50, and so forth, while the rules governing the conditions of issuance of provisional attachment orders are regulated under the Enforcement and Bankruptcy Law numbered 2004 (EBL) Article 257, and so forth. Pursuant to Article 257 of the EBL, a distinction is made between those receivables that are due and those other receivables that are not due in terms of the conditions needed for the issuance of a provisional attachment order. Nevertheless, there is no specific provision under Turkish law regarding receivables that are subject to a foreign court judgement whose enforcement is yet to be requested or finalised before Turkish courts. The determination of whether the receivable is due or not is important in terms of the conditions to be sought for provisional attachment. Furthermore, the relationship between Article 57 (2) of the PIL Code, which envisages that an appeal to the enforcement decision with regard to the foreign court judgement shall suspend the execution of the enforcement decision, and the time limits foreseen regarding the complementary procedures of a provisional attachment order is a debated subject. Moreover, whether foreigners who have deposited a security payment to file an enforcement lawsuit pursuant to Article 48 of the PIL Code will also be required to deposit security for a second time for the issuance of the provisional attachment order pursuant to Article 259 of the EBL is another issue that needs to be clarified. In this paper, initially, the conditions for issuance of provisional attachment orders will be examined. Next, the aforementioned issues will be examined with examples from the practise and the decisions of the Court of Cassation.